Raman spectral variation for human fingernails of postmenopausal women is dependent on fracture risk and osteoporosis status. (8th March 2017) - Beattie, J. R.; Caraher, M. C.; Cummins, N. M.; O'Driscoll, O. M.; Eastell, R.; Ralston, S. H.; Towler, M. R.
Abstract : Patients diagnosed with osteoporosis have reported loss of fingernail resilience as the disease progresses. Keratin is the predominant protein in human nail tissue, and its structure has been postulated to be different in fingernails clipped from subjects who have sustained fragility fractures and those who have not, which may offer a window into the donor's bone health. This study was designed to qualify these differences, which may lead to the development of a novel screening tool for fracture risk. Raman spectroscopy was used to measure the fingernails of 633 postmenopausal women who presented at six fracture clinics located across the UK and Ireland. The Raman signals from donor's fingernails were compared between (1) fracture and nonfracture and (2) osteoporotic versus non‐osteoporotic donors The data presented show differences in the protein changes observed for pervasive osteoporosis compared to a general increased risk of fragility fracture. For fracture risk, compositional changes falling into broad classes of amino acid residue (aliphatic, aromatic, acidic, amide and sulphurous) were observed, while a difference in disulphide bonding levels was reaffirmed. For pervasive osteoporosis, the disulphide mode suggested increasing disorder in disulphide bonding orientation. Fractures were associated with a transition from alpha helical secondary structure to random, while the pervasive osteoporosis cases were associated with a transition to beta sheet structure. General fracture risk is associated with a change in the structure and composition of the keratin protein. Osteoporosis is associated with different protein structural changes and an increase in free acid groups. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Human nail protein structure and composition are affected by systemic factors that are associated with poor bone health. Fracture risk is associated with restructuring of nail keratin and compositional changes. Osteoporosis is associated with changes in the ionization of acid residues in the nail keratin.